2007
DOI: 10.1152/ajprenal.00339.2006
|View full text |Cite
|
Sign up to set email alerts
|

Vasculotropic, paracrine actions of infused mesenchymal stem cells are important to the recovery from acute kidney injury

Abstract: Acute kidney injury (AKI) is a major clinical problem in which a critical vascular, pathophysiological component is recognized. We demonstrated previously that mesenchymal stem cells (MSC), unlike fibroblasts, are significantly renoprotective after ischemia-reperfusion injury and concluded that this renoprotection is mediated primarily by paracrine mechanisms. In this study, we investigated whether MSC possess vasculoprotective activity that may contribute, at least in part, to an improved outcome after ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
456
2
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 589 publications
(499 citation statements)
references
References 44 publications
23
456
2
10
Order By: Relevance
“…59 In another study it was shown that the renoprotective effect of MSCs was mediated by the mitogenic and pro-survival insulin growth factor-1 (IGF-1) produced by the MSCs. 60 Recently, a vasculotropic effect of infused MSC in the kidney was shown, 61 which may be relevant to SSc.…”
Section: Animal Models Of Tissue Protectionmentioning
confidence: 99%
“…59 In another study it was shown that the renoprotective effect of MSCs was mediated by the mitogenic and pro-survival insulin growth factor-1 (IGF-1) produced by the MSCs. 60 Recently, a vasculotropic effect of infused MSC in the kidney was shown, 61 which may be relevant to SSc.…”
Section: Animal Models Of Tissue Protectionmentioning
confidence: 99%
“…19 To this point, MSCs secrete vascular endothelial growth factor, insulin-like growth factor, and hematopoietic growth factor, 20 stimulate endogenous angiogenesis, and have a positive effect on the endothelium. 21 Further, unlike EPCs, MSCs have already been clinically used in an allogeneic fashion, primarily for their indirect regenerative and anti-inflammatory properties, 22,23 and thus can be readily available to clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…12 Mesenchymal stromal cells have also proven useful in preclinical acute kidney injury where they displayed potent anti-apoptotic and cytoprotective effects. 13 Interestingly, in preclinical sepsis models, MSCs not only improved survival and organ function but also showed potent antibacterial effects. 14 Given these organ protective effects as well as the ability to clear pathogens, it is clear that MSCs could have potential benefits for many patients in the perioperative period.…”
Section: Potential Perioperative Applications Of Mscsmentioning
confidence: 99%
“…12 Les cellules stromales mésenchymateuses se sont également avérées utiles dans le traitement des lésions rénales aiguës précliniques, où elles ont démontré d'importants effets anti-apoptotiques et cytoprotecteurs. 13 Il est intéressant de mentionner que, dans des modèles précliniques de sepsis, les CSM ont non seulement amélioré la survie et la fonction des organes, mais ont également démontré de puissants effets antibactériens. 14 É tant donné ces effets protecteurs sur les organes ainsi que leur capacité à éliminer les pathogènes, il est clair que les CSM pourraient avoir des bienfaits potentiels pour de nombreux patients en période périopératoire.…”
Section: Applications Périopératoires Potentielles Des Csmunclassified